Late Cretaceous – early Eocene counterclockwise rotation of the Fueguian Andes and evolution of the Patagonia-Antarctic Peninsula system - Poblete, Fernando; Roperch, Pierrick; Arriagada, Cesar; Ruffet, Gilles; Ramírez De Arellano, Cristobal; Hervé, Francisco; Poujol, Marc (Tectonophysics, 2016)
International audience The southernmost Andes of Patagonia and Tierra del Fuego present a prominent arc-shaped structure: the Patagonian Bend. Whether the bending is a primary curvature or an orocline is still matter of controversy. New paleomagnetic data have been obtained south of the Beagle Channel in 39 out of 61 sites. They have been drilled in Late Jurassic and Early Cretaceous sediments and interbedded volcanics and in mid-Cretaceous to Eocene intrusives of the Fuegian Batholith. The anisotropy of magnetic susceptibility was measured at each site and the influence of magnetic fabric on the characteristic remanent magnetizations (ChRM) in plutonic rocks was corrected using inverse tensors of anisotropy of remanent magnetizations. Normal polarity secondary magnetizations with west-directed declination were obtained in the sediments and they did not pass the fold test. Thesecharacteristic directions are similar to those recorded by mid Cretaceous intrusivessuggesting a remagnetization event during the normal Cretaceous superchron and describea large (>90°) counterclockwise rotation. Late Cretaceous to Eocene rocks of the FueguianBatholith, record decreasing counterclockwise rotations of 45° to 30°. These paleomagneticresults are interpreted as evidence of a large counterclockwise rotation of the FueguianAndes related to the closure of the Rocas Verdes Basin and the formation of the DarwinCordillera during the Late Cretaceous and Paleocene.The tectonic evolution of the Patagonian Bend can thus be described as theformation of a progressive arc from an oroclinal stage during the closure of the RocasVerdes basin to a mainly primary arc during the final stages of deformation of theMagallanes fold and thrust belt. Plate reconstructions show that the Antarctic Peninsulawould have formed a continuous margin with Patagonia between the Early Cretaceous andthe Eocene, and acted as a non-rotational rigid block facilitating the development of thePatagonian Bend.